Childhood asthma is associated with mutations and gene expression differences of ORMDL genes that can interact. Issue 10 (20th July 2015) - Toncheva, A. A.; Potaczek, D. P.; Schedel, M.; Gersting, S. W.; Michel, S.; Krajnov, N.; Gaertner, V. D.; Klingbeil, J. M.; Illig, T.; Franke, A.; Winkler, C.; Hohlfeld, J. M.; et al.
Abstract Background Genomewide association studies identified ORMDL3 as a plausible asthma candidate gene. ORMDL proteins regulate sphingolipid metabolism and ceramide homeostasis and participate in lymphocyte activation and eosinophil recruitment. Strong sequence homology between the three ORMDL genes and ORMDL protein conservation among different species suggest that they may have shared functions. We hypothesized that if single nucleotide polymorphisms (SNPs) in ORMDL3 alter its gene expression and play a role in asthma, variants in ORMDL1 and ORMDL2 might also be associated with asthma. Methods Asthma associations of 44 genotyped SNPs were determined in at least 1303 subjects (651 asthmatics). ORMDL expression was evaluated in peripheral blood mononuclear cells (PBMC) from 55 subjects (eight asthmatics) before and after allergen stimulation, and in blood (n = 60, 5 asthmatics). Allele‐specific cis‐effects on ORMDL expression were assessed. Interactions between human ORMDL proteins were determined in living cells. Results Sixteen SNPs in all three ORMDLs were associated with asthma (14 in ORMDL3). Baseline expression of ORMDL1 (P = 1.7 × 10−6) and ORMDL2 (P = 4.9 × 10−5) was significantly higher in PBMC from asthmatics, while induction of ORMDLs upon stimulation was stronger in nonasthmatics. Disease‐associated alleles (rs8079416, rs4795405, rs3902920) alter ORMDL3 expression. ORMDL proteins formed homo‐ and heterooligomers and displayed similar patterns of interaction with SERCA2 and SPT1. Conclusions Polymorphisms in ORMDL genes are associated with asthma. Asthmatics exhibit increased ORMDL levels, suggesting that ORMDLs contribute to asthma. Formation of heterooligomers and similar interaction patterns with proteins involved in calcium homeostasis and sphingolipid metabolism could indicate shared biological roles of ORMDLs, influencing airway remodeling and hyperresponsiveness.